Removal of tetracycline antibiotic from aqueous solution using bimetallic CuCo-ZIFs as an efficient catalyst in the presence of hydrogen peroxide - Thu Le; Bao Tran; Ngoc Tri Tan Ho; Luu Ngoc Hanh Cao; Truong Ngoc Mai Ngo; Huynh Vu Thanh Luong; Huynh Giao Dang (CTU Journal of Innovation and Sustainable Development)
Antibiotics play an important role in disease treatment; however, they are also a threat to public health and the ecosystem. Therefore, a bimetallic CuCo-ZIFs catalyst was manufactured through the ultrasonic-assisted solvothermal method to activate H2O2 towards the removal of tetracycline (TC) in an aqueous environment, a polluting broad-spectrum antibiotic model. PXRD, SEM, TEM, EDX, TGA, FT-IR, and BET analyses indicated that CuCo-ZIFs cubic crystals were successfully synthesized with high crystallinity, large specific surface area, and ideal thermal stability. Factors affecting the TC removal were investigated, including CuCo-ZIFs dosage, H2O2 concentration, treatment time, initial TC concentration, and reaction temperature. The results showed that the CuCo-ZIFs/H2O2 catalytic system was capable of effectively handling TC, with about 93.9% of TC removed in the presence of 0.3 g.L-1 CuCo-ZIFs, 0.01 mol.L-1 H2O2 at room temperature within 30 min. Conclusively, this study contributes to expanding the application potential of bimetallic CuCo-ZIFs materials to eliminate antibiotic residues in an aqueous environment and inspire research on environmental improvement.